Analysis of International Trade in Promoting Economic Growth in Indonesia - Azulaidin A (Madani: Jurnal Ilmiah Multidisiplin, 2026)
An increase in economic growth is driven by higher investment, which is a key factor in enhancing Indonesia’s competitiveness at both regional and global levels. In this context, the manufacturing industry plays an important role as it has become a primary driver of the economy. This study aims to examine the effects of the exchange rate, world oil prices, China’s economic growth, United States economic growth, and foreign investment on Indonesia’s economic growth through agricultural exports, industrial exports, and imports. The findings indicate that the exchange rate, world oil prices, China’s economic growth, and United States economic growth influence Indonesia’s economic growth. However, foreign direct investment does not have a significant effect on Indonesia’s economic growth. This study suggests that appropriate policies to stabilize the rupiah exchange rate, investment, and international trade will ultimately enhance productivity and promote Indonesia’s economic growth.